How to Achieve Inclusive Growth - Valerie Cerra; Barry Eichengreen; Asmaa Adel El-Ganainy; Martin Schindler (Oxford University Press, 2022)
Rising inequality and widespread poverty, social unrest and polarization, gender and ethnic disparities, declining social mobility, economic fragility, unbalanced growth due to technology and globalization, and existential danger from climate change are urgent global concerns of our day. These issues are intertwined. They therefore require a holistic framework to examine their interplay and bring the various strands together. This book brings together leading academic economists and experts from several international institutions to explain the sources and scale of these challenges. The book summarizes a wide array of empirical evidence and country experiences, lays out practical policy solutions, and devises a comprehensive and unified plan of action for combatting these economic and social disparities. This authoritative book is accessible to policy makers, students, and the general public interested in how to craft a brighter future by building a sustainable, green, and inclusive society in the years ahead.
Keywords: 330; Inclusive growth; growth; inequality; equality; poverty; development; climate change; disparities; income distribution; economic policy; Inklusives Wachstum; Soziale Ungleichheit; Soziale Gerechtigkeit; Soziale Integration; Armutsbekämpfung; Wirtschaftspolitik; Welt